Identity capital and future concerns in urban adolescents from La Araucanía-Chile - Neira-Escalona, Yosyua; Bravo-Sanzana, Mónica; Terán-Mendoza, Oscar; Miranda, Rafael (Frontiers in Education, 2024)
Late modernity influences the construction and constitution of identity and the management of adolescents' future lives. Research has shown that identity capital predicts the resolution of a successful identity; however, in Latin America, no antecedents have conducted studies under this conceptual framework. This study aimed to analyze the relationship pattern between identity capital components and future concerns. The participants were 703 adolescents between 15 and 19 years of age who, in the year 2021, were in the third and fourth year of high school in urban educational establishments in La Araucanía-Chile, to whom questions from the Governance of Educational Trajectories in Europe (GOETE) adapted to the Chilean context and the general self-efficacy scale were applied. Confirmatory factor analyses were performed to determine the suitability of the indicators to measure the constructs of interest, and a structural equation analysis to determine the pattern of relationships between variables. The final model obtained excellent indicators of goodness of fit [χ² (422) = 965.858, p < This is a provisional file, not the final typeset article 0.001; CFI = 0.977; TLI = 0.975; RMSEA= 0.043; SRMR= 0.056] in which it is evident that parental support and interaction are related with self-efficacy and self-concept and these in turn with adolescents' future concerns. Implications of the findings are discussed, and the results are expected to guide educational institutions.